KSTAR PFC와 진공용기의 가열탈리 단계에서의 온도특성에 관한 연구 - 유성연(Seong-Yeon Yoo); 김영진(Young-Jin Kim); 정남용(Nam-Yong Jung); 김경민(Kyung-Min Kim); 이제묘(Je-Myo Lee) (설비공학 논문집, 27(3), 2015)
To create an ultra-high vacuum state at the KSTAR, the temperature of plasma facing component and vacuum vessel should be maintained at $300^{°}C$ and $110^{°}C$ respectively at a baking phase. The purpose of this research is obtaining the target baking temperatures. Experiments were performed to investigate the temperature characteristics of PFC and VV at the baking phase. Thermal network analysis was used to find heat transfer rates among PFC, VV and other components, and this analysis was verified by using the experimental data. The required heating energy of the PFC and the heating and cooling energy of the VV for the target baking temperatures were found to be 346 kW, 28 kW, and 136 kW, respectively.